2013
DOI: 10.1037/a0029279
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary meta-analysis of the potential antecedents, correlates, and consequences of protégé perceptions of mentoring.

Abstract: This meta-analysis summarized youth, academic, and workplace research on the potential antecedents (demographics, human capital, and relationship attributes), correlates (interaction frequency, relationship length, performance, motivation, and social capital), and consequences (attitudinal, behavioral, career-related, and health-related outcomes) of protégé perceptions of instrumental support, psychosocial support, and relationship quality to the mentor or to the relationship. A total of 173 meta-analytic corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
554
5
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(593 citation statements)
references
References 277 publications
(383 reference statements)
27
554
5
7
Order By: Relevance
“…Our work adds to the body of scholarship on academic mentoring which Eby et al [5] reported as being a largely understudied area in the mentoring literature. Inspired by previous findings (e.g.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our work adds to the body of scholarship on academic mentoring which Eby et al [5] reported as being a largely understudied area in the mentoring literature. Inspired by previous findings (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…These DMP items focus on the instrumental support function of mentoring rather than the psychosocial support function [5,16]. The other set of PCs was derived from the 16 items that made up our list of DRE.…”
Section: Core Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work motivation is a psychological process influencing the allocation of personal efforts and resources related to work (Kanfer, Chen & Pritchard, 2008). Eby and her colleagues (Eby et al, 2013;Eby, Allen, Evans, Ng & DuBois, 2008) showed that mentoring can significantly increase protégé's work motivation such as hours worked, persistence, or job involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Chua, Ingram & Morris, 2008;Ergeneli, Ari & Metin, 2007). Interpersonal trust can be the new avenue for mentoring research (Eby et al, 2013;Kram & Ragins, 2008), because of the relational qualities embedded in a mentoring relationship (Ragins, Cotton & Miller, 2000). However, at many of the studies relationship quality has been conceptualized in terms of relationship satisfaction or relational support (Eby et al, 2008).…”
Section: Introductionmentioning
confidence: 99%